2017
DOI: 10.3389/fpls.2017.01068
|View full text |Cite
|
Sign up to set email alerts
|

CaRDR1, an RNA-Dependent RNA Polymerase Plays a Positive Role in Pepper Resistance against TMV

Abstract: RNA silencing functions as a major natural antiviral defense mechanism in plants. RNA-dependent RNA polymerases (RDRs) that catalyze the synthesis of double-stranded RNAs, are considered as a fundamental element in RNA silencing pathways. In Arabidopsis thaliana, RDR1, 2 and 6 play important roles in anti-viral RNA silencing. Expression of RDR1 can be elevated following plant treatment with defense hormones and virus infection. RDR1 has been studied in several crop species, but not in pepper (Capsicum annuum L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 77 publications
(120 reference statements)
0
21
0
Order By: Relevance
“…119,120 Furthermore, ABA exogenous application increases the resistance of plants against viruses such as TMV and Tobacco necrosis virus (TNV) by hindering the virus movement. [121][122][123] Another phytohormone which is closely linked to the closure of PD is SA. Specifically, SA exogenous application results in the deposition of callose within PD.…”
Section: Virus Attacking Strategies and Phytohormonesmentioning
confidence: 99%
“…119,120 Furthermore, ABA exogenous application increases the resistance of plants against viruses such as TMV and Tobacco necrosis virus (TNV) by hindering the virus movement. [121][122][123] Another phytohormone which is closely linked to the closure of PD is SA. Specifically, SA exogenous application results in the deposition of callose within PD.…”
Section: Virus Attacking Strategies and Phytohormonesmentioning
confidence: 99%
“…Recently, it was found that Tobacco mosaic virus-coat protein (TMV-CP) accumulation was less in the CaRDR1 overexpressing tobacco lines following TMV infection. Furthermore, TMV inoculation enhanced transcript levels of AGOs and DCls genes in the RDR1 expressing lines [136]. Similarly, MdRDR1 transgenic tobacco plants enhanced resistance against TMV, Sunn hemp mosaic virus and Turnip vein-clearing virus [137,138].…”
Section: Plant Rna Silencing and Virusesmentioning
confidence: 99%
“…In the case of CMV, the siRNAs production depends on the RDR1, and these secondary vsiRNAs are important for antiviral silencing [88]. Silencing of RDR1 or knockout rdr1 mutants result in a higher level of virus RNA and reduces resistance in pepper, Arabidopsis , maize, and tomato plants [136,139,140,141], however, the resistance of potato to PVX and PVY is not compromised [142]. As we mentioned, RDR2 protein along with DCL3 is involved in the production of 24 nt siRNAs, and loss of RDR2 function causes extensive changes in the expression of genes, transposons and 24 nt sRNAs [61].…”
Section: Plant Rna Silencing and Virusesmentioning
confidence: 99%
“…In previous study, we cloned CaRDR1 from pepper, which was induced by salicylic acid (SA) and tobacco mosaic virus (TMV). CaRDR1 played a positive role in pepper TMV resistance by regulating antioxidant enzymes’ activities and the expression of RNA silencing-related genes [ 18 ]. In this study, the expression pattern of pepper AGO , DCL and RDR gene families were examined in response to biotic/abiotic stress.…”
Section: Introductionmentioning
confidence: 99%